MEDIA AND SPACE DISCLOSURES OF THE POWER COURT - Taufik, Cevi (Jurnal Komunikasi dan Bisnis, 2021)
The era of the third wave of media can reveal the dark dimensions of power. Private spaces that are hidden behind arrogant individuals are drawn into public spaces to become important topics. There is no secret other than the spread of issues on various media platforms. Various coverage from personal dimensions to policy areas is clearly revealed. Furthermore, to find out the background behind it, this study uses descriptive qualitative methods with the aim of obtaining data in order to explain the phenomena which is the theme of this research. From the results of the research analysis shows that the media are able to reveal dark spaces of power to the ability to eliminate practices that occur in them.